TRANSFORMASI PENDIDIKAN DASAR MELALUI SEKOLAH RESPONSIF GENDER: STUDI EKSPERIMEN TERHADAP PENINGKATAN KESETARAAN DAN INKLUSI - Wachidah, Kemil; Ahmad Fathoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Basic education plays an important role in shaping children's character and mindset from an early age. However, the implementation of gender-responsive school principles in many elementary schools still faces various challenges, such as gender stereotypes embedded in learning materials and biased social interactions, as well as limited understanding among teachers and supporting facilities. This study aims to analyze the impact of gender-responsive school interventions on improving equality and inclusivity at SD Muhammadiyah 1 Candi Labschool UMSIDA. The method used is an experimental study with a pretest-posttest one-group design, measuring attitudes, knowledge, and gender-responsive practices before and after the intervention. The primary instruments are questionnaires analyzed quantitatively using descriptive and inferential statistics, as well as qualitative data from interviews and observations analyzed thematically. The results of the study showed significant improvements in various aspects, including formal gender-responsive school policies, budget allocation for learning and extracurricular activities that support gender equality, and the integration of gender values in lesson plans. Additionally, the participation of male and female students became more balanced, and learning materials began to eliminate gender stereotypes. Although accessibility to facilities for persons with disabilities still needs improvement, teachers' awareness and competence on gender and inclusion issues have increased sharply. This training serves as an important foundation for the sustainable development of gender-responsive schools, while also opening opportunities for other schools to adopt similar approaches to achieve inclusive and equitable education.